Pengaruh Kualitas Pelayanan, Keragaman Produk, Dan Suasana Café Terhadap Kepuasan Konsumen Di Akar Coffee Wates - Rizki Winda Puspita Sari; Edi Murdiyanto; Zaenul Muttaqien (Journal of Creative Student Research, 2023)
A form of strategy to influence consumer satisfaction can be done by providing good quality service. Consumers feel that what they want will be served responsively, besides this, the variety of products available will fulfill consumers' taste desires. A comfortable cafe atmosphere can make consumers feel satisfied and want to make repeat purchases. The aim of this research is to determine the influence of service quality, product diversity and cafe atmosphere on consumer satisfaction at Akar Coffee Wates. This research uses a quantitative approach with a sample of 112 respondents. From the results of the t test, service quality has a significant effect on consumer satisfaction with a sig value of 0.000 < 0.05, so H0 rejected and Ha accepted. Then product diversity has a significant effect on consumer satisfaction with a sig value of 0.000 < 0.05, so H0 rejected and Ha accepted. And the atmosphere of the cafe has a significant effect on consumer satisfaction with a sig value. 0.000 < 0.05 then H0 rejected and Ha accepted. In the F test results, a Sig value of 0.000 <0.05 is obtained, so H0 rejected and Ha accepted, meaning that service quality, product diversity and cafe atmosphere simultaneously influence consumer satisfaction at Akar Coffee Wates.